Brief Report: Changes in Antiphospholipid Antibody Titers During Pregnancy: Effects on Pregnancy Outcomes. Issue 8 (27th July 2016) - Yelnik, Cecile M.; Porter, T. Flint; Branch, D. Ware; Laskin, Carl A.; Merrill, Joan T.; Guerra, Marta M.; Lockshin, Michael D.; Buyon, Jill P.; Petri, Michelle; Sammaritano, Lisa R.; Stephenson, Mary D.; Kim, Mimi Y.; et al.
Abstract : Objective: To measure variance in antiphospholipid antibody (aPL) levels during pregnancy and to determine if variation affects pregnancy outcomes. Methods: We used data from the PROMISSE (Predictors of Pregnancy Outcome: Biomarkers in Antiphospholipid Antibody Syndrome and Systemic Lupus Erythematosus) study, a multicenter prospective study of pregnant women with aPL and/or systemic lupus erythematosus (SLE). Antiphospholipid antibodies were considered present if any of the following were positive: anticardiolipin (aCL), anti–β2 ‐glycoprotein I (anti‐β2 GPI) titers ≥40 IgG phospholipid (GPL) or IgM phospholipid (MPL) units, and/or lupus anticoagulant (LAC). Antiphospholipid antibodies were measured every trimester and postpartum. Adverse pregnancy outcomes were defined as fetal/neonatal death, preterm delivery (<36 weeks) due to preeclampsia or placental insufficiency, or growth restriction. Results: One hundred fifty‐two aPL‐positive patients were studied. Fifty‐seven percent had clinical antiphospholipid syndrome (APS) and 36% had SLE. IgG aPL levels were significantly lower during the second and third trimesters compared to initial screening, but IgG aCL and anti‐β2 GPI remained high‐positive through pregnancy in 93% of patients during the second trimester, and in 85% of patients during the third trimester. IgM aPL titers were negative in the majority of patients and decreased modestly during pregnancy among patients who were positive. LAC frequency also decreased, but 75% of patients remained positive through the second trimester. Only 4% of patients with aPL at baseline did not have aPL in either the second or third trimesters. Changes in aPL levels or aPL status were not associated with adverse pregnancy outcomes. LAC was the only aPL associated with adverse pregnancy outcomes. Conclusion: The aPL in the cohort decreased marginally during pregnancy, and changes were not associated with pregnancy outcomes. Our results suggest that, among women with aPL and/or SLE, measuring aPL early in pregnancy is sufficient to assess risk. Repeat aPL testing through pregnancy is unnecessary.